2004
DOI: 10.1007/s00595-003-2687-z
|View full text |Cite
|
Sign up to set email alerts
|

Less Invasive Surgery for Primary Hyperparathyroidism Based on Preoperative 99m Tc-hexakis-2-methoxyisobutylisonitrile Imaging Findings

Abstract: The sensitivity of MIBI to adenoma was thus found to be highly satisfactory. As a result, it might be possible to perform less invasive surgeries based on MIBI imaging without any decrease in the surgical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…There are reports stating that weight alone in sHPT does not account for the lesser likelihood of detection by MIBI; other factors such as fewer mitochondria, poor vascularity, and altered metabolic conditions seen in patients suffering from chronic renal disease could have led to the inadequate distribution and concentration of MIBI [43,44]. Our study seems to favor the contention of other authors who have suggested that a signifi cant correlation exists between scintigraphic fi ndings and the size/weight of the glands [32,45,46]. In our study, non-signifi cant differences in the weight of the glands between pHPT and sHPT could have led to similar sensitivity values in this different clinicopathologic setting.…”
Section: Discussionsupporting
confidence: 80%
“…There are reports stating that weight alone in sHPT does not account for the lesser likelihood of detection by MIBI; other factors such as fewer mitochondria, poor vascularity, and altered metabolic conditions seen in patients suffering from chronic renal disease could have led to the inadequate distribution and concentration of MIBI [43,44]. Our study seems to favor the contention of other authors who have suggested that a signifi cant correlation exists between scintigraphic fi ndings and the size/weight of the glands [32,45,46]. In our study, non-signifi cant differences in the weight of the glands between pHPT and sHPT could have led to similar sensitivity values in this different clinicopathologic setting.…”
Section: Discussionsupporting
confidence: 80%
“…Pulmonary lipomas within the peripheral parenchyma are exceedingly rare. 2, 3 We report such a case.…”
Section: Lipoma Pulmonar Intraparenquimatoso Con Comportamiento Clínimentioning
confidence: 81%
“…Ectopic parathyroid adenomas of less than 10 mm in diameter are best detected with 99m Tc-MIBI scintigraphy. 3 Cervical ultrasound, CT and magnetic resonance imaging are used to determine the exact anatomical site of the mass.…”
Section: Discussionmentioning
confidence: 99%
“…Taira, et al reported the usability of high-resolution CT with 99m Tc-MIBI scintigraphy for the detection of ectopic mediastinal parathyroid adenomas less than 10 mm in diameter. 6) We identified the ectopic adenoma using both 99m Tc-MIBI scintigraphy and conventional chest CT.…”
Section: Discussionmentioning
confidence: 99%